Pengaruh Diterbitkannya Perppu Nomor 1 Tahun 2020 Terhadap Stabilitas Sistem Keuangan Bank Syariah Di Indonesia - ely nurhayati; Amin Mansur; Hesty Juni Tambuati Subing (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2023)
The Covid-19 pandemic has shaken the national economy. This causes the wheels of the economy to not run, so that the business world loses demand and at the same time loses the ability to create supply. The spread of the corona virus has disrupted the performance and capacity of debtors from the business community in carrying out their credit obligations so that it has the potential to disrupt banking performance in managing credit which in turn can disrupt the stability of Islamic banks. One of the government's efforts to minimize the impact of the Covid-19 pandemic outbreak on the country's economy including the financial sector is to ratify Perppu No. 1 of 2020. This study analyzes how the effect of the issuance of Perppu No. 1 of 2020 has on the stability of the financial system of Islamic banks in Indonesia. The method used in this research is descriptive analysis method. The results of the analysis found that the issuance of Perppu No. 1 of 2020 has so far not had an impact on the stability of the financial system of Islamic banks in Indonesia. This is due to the fact that during the Covid-19 pandemic, no sharia bank has experienced a serious enough shock so that the various facilities offered through the Perppu have not been utilized by sharia banking